QUESTIONING THE BODY AT SCHOOL: REFLECTIONS ON CHILDHOOD OBESITY (Fiep Bulletin - online, 2016)
The body, in the school enviromnent, constitutes one of the fundamental concerns of all  physical education professionals, as well as of other educators at school, regarding human nature. This year's congress inspires us to discuss the obese children's body at school. As it cannot be thoroughly approached in this paper, we believe that reflection focused on the conceptual nucleus "body" and "obesity", generally, is little presented in the daily discussions of these professionals within the schools. These concepts are rarely included in teacher training processes for children's education and early years of elementary school.We discuss the body conception present in the school environment, derived from the so- called "Cartesian model", anchored in the principles of "disjunction", "reduction" and "abstraction", which prevail in the organization of time and space at school. We also mention in our reflections the fragmentation of the body which, in the media aimed at different age groups, respond to several market interests.Finally, we aim at discussiong the definition of obesity and its consequences in the learning process. We state that it is crucial to strengthen the school-family partnership in order to stimulate new educational practices aiming at promoting and extending the reflection on body, obesity and other topics under discussion in society, often missing within the school.
Keywords: Body. Children obesity. School